Optimalisasi Proses Sintesis Dan Karakterisasi Biodiesel Dari Minyak Alga Merah (Eucheuma cottonii) Dengan Katalis Kalium Hidroksida (KOH) - Muhammad Zakir; Indah Raya; Asbia Asbia (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2010)
Research on the optimalization of synthesis process of biodiesel as an alternative fuel from red algae oil (Eucheuma cottonii) with potasium hidroksida (KOH) had been done. Red algae (E. cottonii) oil was used as raw material in the Biodiesel synthesis. Red algae oil was gained through extraction process with soxhletation method using n-heksane as solvent. Biodiesel (methyl ester) had been synthesized from red algae oil by transesterification process used methanol as solvent and KOH as catalyst. The process had been done at 40, 50, 60, and 70 oC with reaction time 2, 3, 4, and 5 hours. The total fatty acids and free fatty acids of the product were used in the calculation of conversion value. The optimum temperature and reaction time giving the greatest number of biodiesel conversion is 60 0C for 4-5 hours with conversion 24,1077%. The biodiesel of highest conversion was characterized physically and chemically. The Result showed that viscosity, density, water value, and iodine number were 4,432 cSt, 0,8383 g/mL, 0,013, and 10,66 mg/mek, respectively. Biodiesel from red algae oil that was not effective to be used as alternative fuel because of its product is very low.Keywords: Biodiesel fuel, Eucheuma cottonii, transesterification, KOH